Intertextual Analysis Of The Novel When Love Is Particular By Habiburrahman El Shirazy And The Novel Ranah 3 Colors By Ahmad Fuadi - Yuwono, Muhammad Adrian; Irwansyah, Irwansyah (International Journal of Social Sciences, 2025)
This study analyzes intertextuality and structure in two popular Indonesian novels, namely When Love Recites the Rosary by Habiburrahman El Shirazy and Ranah 3 Warna by Ahmad Fuadi. The main objective of this study is to describe the structural components of both novels and identify the intertextual relationships between them. By using a qualitative descriptive method through a content analysis approach, this study examines the themes, characters, settings, and life values ​​contained in both literary works. The results of the study indicate a strong intertextual relationship between the two novels, which can be seen from the similarity of the theme of struggle, the main character who is tough and religious, and the values ​​of faith, education, and resilience. These two novels effectively represent the spirit of the young generation of Indonesia in fighting for their ideals through education and spirituality.